2002
DOI: 10.1118/1.1521940
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of CT‐based thickness measurement of thin structures: Modeling of limited spatial resolution in all three dimensions

Abstract: Measurement of the width of thin structures such as the cortical shell of the vertebral body or femoral neck with computed tomography (CT) is limited by the spatial resolution of the CT system. Limited spatial resolution exists both within the CT image plane and perpendicular to it and can be described by the in-plane point spread function (PSF) and the across-plane slice sensitivity profile (SSP), respectively. The goal of this study was to confirm that errors of thickness measurement of thin structures criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
125
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(127 citation statements)
references
References 17 publications
(14 reference statements)
1
125
1
Order By: Relevance
“…While the QCT measurement of human femur distinguishes between cortical and trabecular bone, partition of the femur into trabecular and cortical regions based on the empirical separation threshold (HU>600) may generate a certain inaccuracy in the cortical bone thickness, which can play an important role in bone resistance to fracture [9]. The accuracy of the cortical thickness measurement with QCT depends on the spatial resolution of the CT system, image noise, the positioning of specimens and the image processing software [59]. Also, Lee et al [41] and Popescu et al [60] reported that the spatial registration between CT scans of a patient's organ and the computer model of the organ is still a critical step in most computer-aided models accuracy.…”
Section: Fracture Simulation Of Proximal Femur Under One-legged Stancmentioning
confidence: 99%
“…While the QCT measurement of human femur distinguishes between cortical and trabecular bone, partition of the femur into trabecular and cortical regions based on the empirical separation threshold (HU>600) may generate a certain inaccuracy in the cortical bone thickness, which can play an important role in bone resistance to fracture [9]. The accuracy of the cortical thickness measurement with QCT depends on the spatial resolution of the CT system, image noise, the positioning of specimens and the image processing software [59]. Also, Lee et al [41] and Popescu et al [60] reported that the spatial registration between CT scans of a patient's organ and the computer model of the organ is still a critical step in most computer-aided models accuracy.…”
Section: Fracture Simulation Of Proximal Femur Under One-legged Stancmentioning
confidence: 99%
“…This may be caused by the finite width of PSF (25,28,29). Thus, we propose a new measurement method that greatly reduces PSF induced bias by incorporating PSF directly into thickness measurement.…”
Section: Discussionmentioning
confidence: 99%
“…It can be assumed that a PSF is separable into a two‐dimensional (2D) PSF in the xy scan plane and a slice sensitivity profile (SSP) in the z direction perpendicular to the scan plane 12 , 14 . Then, the three‐dimensional (3D) CT image I(x, y, z) can be expressed as follows: Ifalse(x,y,zfalse)=false(Ofalse(x,y,zfalse)PSFfalse(x,yfalse)false)SSPfalse(zfalse) …”
Section: Methodsmentioning
confidence: 99%
“…Several studies 12 , 14 have performed the above computer simulations. In those simulations, the PSFs, SSPs, and object functions were treated as discrete (digital) data; however, the interval of the discrete data was not specified.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation